The Influence of User-Generated Content on E-Commerce Sales: A Meta-Analysis - Harsandaldeep Kaur (Innovative Research Thoughts, 2024)
User-generated content (UGC) has become a common element of e-commerce platforms, with customers increasingly depending on reviews, ratings, and other kinds of UGC to make purchase choices. While the effect of user-generated content (UGC) on e-commerce sales is generally acknowledged, its quantity and consistency are still debated. This meta-analysis combines data from previous research studies to give a full knowledge of the link between user-generated content and e-commerce sales. Using a variety of empirical research and theoretical frameworks, we investigate the implications of UGC qualities, platform features, and contextual variables on e-commerce revenue success. Our findings provide useful insights into the elements that influence the effect of user-generated content on sales, such as product category, brand reputation, and customer characteristics. Furthermore, we highlight gaps in the current literature and offer future study directions to help us better understand the complicated interaction between user-generated content and e-commerce purchases.